Application of Kalman Filter on Gyroscope to Reduce Noise and Improve Responsiveness in Shooting Simulator System - Rokhim Utomo; Winardi Aries Tadianta M (International Research & Development for Human Beings (IRDH), 2025)
Shooting simulators are essential tools in military exercises, enabling soldiers to develop their shooting skills in a controlled and safe environment. However, the effectiveness of these simulators is often hindered by noise in gyroscope sensor data, which is used to track weapon motion. This noise can lead to inaccuracies in determining the position and orientation of the weapon, thereby reducing the precision of aiming and the realism of the simulation. In turn, this affects the responsiveness and overall performance of the training system, potentially diminishing the quality of soldiers’ practice sessions. To address this issue, the implementation of a Kalman filter proves to be highly effective. By processing noisy gyroscope data, the Kalman filter minimizes inaccuracies, enhances motion tracking, and ensures smoother and more realistic weapon handling during simulation. This improvement not only boosts the accuracy of the simulator but also ensures a more reliable and responsive training experience for soldiers